Clinical Presentation and Risk Factors of Venous Thromboembolic Disease. Issue 3 (July 2017) - Alhassan, Sulaiman; Pelinescu, Anca; Gandhi, Viral; Naddour, Mouhib; Singh, Anil C.; Bihler, Eric
Abstract : Venous thromboembolism (VTE) has a wide range of clinical presentations. Deep venous thrombosis may occur in upper or lower extremities or in visceral veins. Extremity deep venous thrombosis usually manifests with unilateral painful swelling in the limb, while visceral deep venous thrombosis manifestations vary on the basis of the involved organ. Pulmonary embolism classically manifests with sudden pleuritic chest pain and unexplained dyspnea. Superficial thrombophlebitis usually presents with acute inflammation around a palpable thrombosed superficial vein. Risk factors of VTE are either inherited or acquired. The inherited causes of VTE tend to be familial and more common in younger patients. The common acquired risk factors of VTE include previous history of venous thrombosis, immobilization, recent surgery or trauma, malignancy, and pregnancy. Identifying high-risk patients for VTE based on these risk factors is the cornerstone to provide the prophylactic treatment to prevent thrombotic events.